Interviewing Sergio Bermúdez (Journal of Parents and Teachers, 2014)
Padres y Maestros interviews the actor and presenter Sergio Bermúdez, who confesses his early vocation for dramatic art, and emphasizes the fact that it is not done in schools, even though it would bring benefits such as loss of shame or increased cohesion of the class. He also talks about the important of representatives, offers advice to young artists, and discusses his future projects.
Keywords: Interview; actor; dramatic art; benefits.